Unstable agriculture and droughts : implications for policy - "Rao, C. H. Hanumantha" (New Delhi, 1988)
In the pre-independence period, Indian agriculture was usually described as a gamble in monsoons. There used to be a great deal of uncertainity about crop prospects, as monsoons played a decisive role in determining agricultural output and their failures used to result in widespread famine and misery. Forty years after independence, the Indian agricultural scene, though vastly different, bears certain similarities with its pre-independence past.
Keywords: Agriculture Economic aspects